(untitled) (ACTA MEDICA PERUANA, 2021)
Chylous ascites (CA) is a rare condition, and it can present as a peritoneal reaction named acute chylous peritonitis (ACP). We report the case of a 26-year old male who developed acute abdomen. He underwent surgery and turbid milky fluid was found in his abdominal cavity. A prophylactic appendectomy was performed, as well as aspiration and lavage of the abdominal cavity. Drainage tubes were placed. Studies of the fluid revealed increased triglyceride and amylase contents. Gram-staining and cultures were negative. A computed tomography scan revealed acute pancreatitis (Balthazar C), so a diagnosis of chylous ascites secondary to pancreatitis was confirmed. The patient did well, he received hydration, analgesics, and oral diet according to tolerance. Very few cases of ACP have been reported in the literature, and its association with acute pancreatitis is very unusual. This condition may resemble surgical acute abdomen, and its management includes surgical exploration with peritoneal drainage. Nutritional support may also be needed.